Antioxidant profile of several local rice varieties from Central Java, Indonesia, under biotic stress conditions of bacterial leaf blight - MUHAMMAD AJI CAHYADI; AHMAD YUNUS (Asian Journal of Agriculture, 2025)
Abstract. Cahyadi MA, Yunus A. 2025. Antioxidant profile of several local rice varieties from Central Java, Indonesia, under biotic stress conditions of bacterial leaf blight. Asian J Agric 9: 368-376. Central Java harbors diverse local rice germplasm that requires preservation, yet their resistance to bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) remains underexplored. Antioxidant activity has been linked to BLB resistance, indicating its potential as a screening tool for identifying tolerant varieties in breeding programs. This study examined four local rice varieties inoculated with Xoo, focusing on catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), total flavonoids, and total phenolic compounds. Based on lesion length, Mentik Susu (MS) and Rojolele (RL) were resistant, while Merah Segreng (MSeg) and Hitam Mutiara (HM) showed moderate resistance. At 5 days post-inoculation (dpi), the highest CAT activity (0.019 units/mg protein) occurred in MSeg, while at 20 dpi HM showed the highest (0.014 units/mg protein). For POD, RL exhibited the highest activity (0.271 units/mL protein) at 5 dpi, and MSeg at 20 dpi (0.436 units/mL protein). The highest SOD activity at 5 dpi was observed in HM (169.35 units/mg protein), whereas MS peaked at 20 dpi (157.95 units/mg protein). These enzymatic antioxidant levels did not differ significantly among varieties, but non-enzymatic antioxidants—flavonoids and phenolics—showed significant variation, with MS and RL containing 44.30 and 27.09% more flavonoids and 25.88 and 18.91% more phenolics, respectively, than moderately resistant varieties. These findings indicate that non-enzymatic antioxidants contribute more prominently to BLB resistance than enzymatic ones, and that varieties rich in flavonoids and phenolic compounds, such as Mentik Susu and Rojolele, have stronger resistance, highlighting their potential for breeding programs to enhance tolerance against bacterial leaf blight while supporting the conservation and utilization of Central Java’s local rice diversity.